PEMBERIAN KOMPOS TKKS DAN PUPUK P TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Fauzi, Amat; Puspita, Fifi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to find out the interaction of compost TKKS and P fertilizer as well as finding the best dozage of chose on the growth of oil palm seedling (Elaeis guineensis Jacq.). This research was carried out at the Agricultural Faculty University of Riau Bina Widya Campus KM 12,5 Simpang Baru Tampan district, Pekanbaru. This research was 4 month start in August 2016 through Nopember 2016. This research utilize CRD (Completely Roudomized Design) which 2 factors. First factor is compositing of TKKS wich 3 level. Second factor is fertilizer P dozage wich 3 level. Both factor gave 9 treatment combination and wich 3 replication, so there are 27 experimental units. Each experimental units have 2 seedling, so that there were 54 seedling. Parameters observed were the plant height, number of leaves, seedling diameter, leaf area, root volume of seedlings, dry weight of seedling and root canopy ratio. Data were analyzed statiscally with variance and continued with Duncan New Multiple Range Test (DNMRT) at 5% level. The result of this research showed the interaction of compost fertilizer TKKS and P fertillizer give good influence to all parameters such as plant height, number of leaves, stem diameter, leaf area, root volume of seedling, dry weight of seedling and root canopy area in oil palm nursery age 7 months. Keyword : Oilpalm, Compost TKKS, Fertilizer P